CHARACTERISTIC OF OSTEOPENIC SYNDROME IN PATIENTS WITH PATHOLOGY OF THE THYROID GLAND USING ULTRASOUND OSTEOMETRY - O. A. Pavlenko; L. B. Nochevnaya; V. D. Zavadovskaya; O. Yu. Kilina (Бюллетень сибирской медицины, 2014)
The study was conducted to investigate state of bone metabolism and bone strength in various pathologies of the thyroid gland. We revealed violations of bone remodeling with a shift in the direction of resorption and formation of reduction of bone strength with in patients with hyperthyroidism and hypothyroidism.